Evaluation of Yield and Yield Components of Eggplant (Solanum melongena L.) Genotypes in the Terai Region of Nepal - Prasad Gotame, Tek; Poudel, Sujata; Lal Shrestha, Surendra; Shrestha, Jiban (International Journal of Environment, 2020)
The productivity of eggplant in Nepal is very low due to lack of high yielding, disease and pests resistant varieties. Eight eggplant genotypes [Parwanipur Selection -1 (PS-1), Pusa Purple Long (PPL), Pokhara Lurki, Lalgulab, Pusa Kranti, Arka Keshav, HRDBRI-012 and HRDBRI-013] were evaluated at on-station research field of Regional Agricultural Research Station, Parwanipur, Bara, and PS -1, PPL, Pokhara Lurki, Lalgulab, Pusa Kranti, and Arka Keshav were evaluated at farmers’ field, Bara and Parsa districts from 2018 to 2019. Results of the on-station experiment showed that genotype PS-1 was the earliest maturing genotype and was harvested at 56 days after transplanting. The number of fruits per plot (9 m2 area) was 189 in Arka Keshav followed by HRDBRI012 (180) and PS-1 (179). The number of marketable fruits per plot (9 m2) was highest in Lalgulab (166) followed by PS-1 (152). The biggest fruit size was recorded in PS-1 (130 g) followed by Pusa Kranti (121 g) and PPL (108 g). The fruit yield was recorded the highest in PS-1 (25.8 mt/ha). The genotype PS-1 was found more resistant to Fusarium wilt and shoot and fruit borer followed by PPL. In farmers field, the highest marketable fruits per plot were produced from PPL followed by Pusa Kranti and PS-1. Similarly, the highest yield and marketable yield were also recorded in PS-1 followed by Pusa Kranti. The genotypes PS-1 and PPL were superior in terms of yield and resistance to disease and pests. Therefore, they could be a promising genotypes for central Terai region of Nepal.